Meeting report: 2nd international conference: antibody incompatible transplantation and transplant infectious disease. (6th August 2013) - Lowe, D.; Higgins, R.; Krishnan, N.
Summary The 2nd International Conference on Antibody Incompatible Transplantation and Transplant Infectious Disease took place at the University of Warwick on 23rd and 24th November 2012. The aims of the meeting were to discuss the pertinent clinical and laboratory issues surrounding antibody incompatible transplantation and to provide a contemporary analysis of transplant infectious disease. This report summarises the key points discussed at the meeting.